Risk of colorectal cancer after detection and removal of adenomas at colonoscopy: population-based case-control study - Brenner, Hermann; Chang-Claude, Jenny; Rickert, Alexander Lothar; Seiler, Christoph; Hoffmeister, Michael (Journal of clinical oncology, 2012)
Purpose: Empirical evidence for recommendations of surveillance intervals after detection and removal of adenomas at colonoscopy is still sparse and mostly based on observations of adenoma recurrence. We aimed to assess risk of colorectal cancer (CRC) according to time since polypectomy and factors that might be relevant for risk stratification. Methods: In a population-based case-control study conducted in Germany, detailed history and results of previous large-bowel endoscopies were obtained by interview and from medical records. Risk of CRC among participants with detection of at least one adenoma at a preceding colonoscopy compared with participants without previous large-bowel endoscopy was assessed according to time since polypectomy among 2,582 cases with CRC and 1,798 matched controls. Results: Adjusted odds ratios (95% CIs) of CRC for participants with polypectomy less than 3, 3 to 5, and 6 to 10 years ago (using participants without previous endoscopy as reference group) were 0.2 (0.2 to 0.3), 0.4 (0.3 to 0.6), and 0.9 (0.5 to 1.5), respectively. Strong, significant risk reduction within 5 years was consistently seen for women and men, younger and older participants, patients with and without high-risk polyps (three or more polyps, at least one polyp ≥ 1 cm, at least one polyp with villous components), and those with and without polypectomy in the right colon. With adjusted odds ratios of 0.1 (0.1 to 0.2), 0.3 (0.2 to 0.5) and 0.4 (0.2 to 0.8) for patients with polypectomy less than 3, 3 to 5, and 6 to 10 years ago, risk reduction was particularly strong for left-sided CRC. Conclusion Extension of surveillance intervals to 5 years should be considered, even after detection and removal of high-risk polyps.